Constitutional Court’s Crisis Management of Akil Mochtar’s Case - Uli Mediana, Cipta; Naryoso, S.Sos, M.Si, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The Constitutional Court is one of the state institutions that conduct independent judicial power to hold a court in order to enforce law and justice in Indonesia that became a proof of state agencies was also not spared from the crisis. The Chairman of the Constitutional Court in 2013, Akil Mochtar caught red-handed by the Corruption Eradication Commission (KPK) for allegedly receiving bribe money for handling election disputes Gunung Mas, Central Kalimantan and elections Lebak, Banten. Since the arrest of Akil Mochtar, the media reports negative opinion, so that this crisis into the acute stage. This study used a qualitative approach and constructivism, this research aims to describe the crisis management strategy of the Constitutional Court to face the negative media reports and described the Constitutional Court’s efforts to restore public trust. The theory used include; Weyerhaeuser Issues Management Process, Crisis Cluster, Image Restoration Theory and Strategy Formulation for Crisis Management. The unit of observation in this study is the Constitutional Court of the Republic Indonesia, and the unit of research analysis are those that directly relate of the handling the crisis of the Constitutional Court of Akil Mochtar’s case. This study found that the Constitutional Court seeks to overcome the crisis by always doing the press conference conducted on an ongoing basis information of the arrest of Akil Mochtar, constitutional judges present testified at the Commission, establish the Honorary Council of the Constitutional Court as a device to monitor constitutional justices, constitutional judges forms Ethics Council, and inviting advocates to report to the Constitutional Court if known some legal lobbying efforts, do a media relations activity by visiting the Liputan6.com’s office. This study concluded that the crisis experience of the Constitutional Court in Akil Mochtar’s case included to crisis public relations, where the crisis is categorized as intentional cluster crisis. Crisis management strategy used by the Constitutional Court, among others; corrective action, mortification, and adaptive change strategy.